Stable isotope profile (C, N, O, S) of Irish raw milk: Baseline data for authentication. (March 2021) - O'Sullivan, Roisin; Monahan, Frank J.; Bahar, Bojlul; Kirwan, Laura; Pierce, Karina; O'Shea, Audrey; McElroy, Shane; Malone, Fionnuala; Hanafin, Brian; Molloy, Sean; Evans, Alexander C.O.; Schmidt, Olaf
Abstract: Grass-based milk production is a major contributor to Irish agricultural output. The study characterized the Irish milk pool using stable isotope ratio analysis of carbon, nitrogen, oxygen and sulphur. Authentic raw milk samples were collected from 50 farms on five occasions over 13 months. Mean values of −27.11, 6.79, −3.27 and 6.16‰ were obtained for δ 13 C, δ 15 N, δ 18 O and δ 34 S, respectively. δ 13 C values reflected a high level of grass input and values increased with increasing cereal concentrate feed input (P < 0.001). δ 18 O values were most negative in spring. There was a significant interaction between feed and season for δ 13 C and δ 15 N values (P < 0.05), with the impact of concentrate feeding most evident in spring. δ 34 S values were lowest at the highest level of concentrate input (P < 0.05). The isotopic values reported here describe the Irish milk pool and may offer the potential to discriminate Irish milk and dairy products from similar commodities from other countries. Highlights: Stable isotope ratio analysis (C, N, O, S) was used to characterize Irish milk. Isotopic values, particularly δ 13 C, reflected a high level of grass feeding. Concentrate impact was clearest in spring, affecting δ 13 C, δ 15 N and δ 34 S values. Isotopic values, particularly δ 18 O, were influenced by season. Farm location (latitude and longitude) influenced δ 18 O and δ 34 S values.